Major element compositions of the plagioclases from andesites from the Kueishantao island analysed by EMPA (S1) - Guo, Kun; Wang, Xiaoyuan; Chen, Shuai (In: Guo, K et al. (2021): In situ elemental, Sr isotope composition of plagioclase and elemental composition of clinopyroxene and thermobarometric data of andesite from Kueishantao, north of Taiwan, China [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.929297, 2021)
This dataset reports in situ major elements of plagioclase of andesite from Kueishantao, north of Taiwan, China. Major element compositions of Pl were obtained with a JEOL JXA-8230 electron microprobe at Ocean University of China.
Keywords: andesite; in-situ mineral geochemistry; plagioclase